2001
DOI: 10.1034/j.1600-0528.2001.290307.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral health promotion in the workplace: the effects on dental care costs and frequency of dental visits

Abstract: It can be concluded that this oral health promotion program in the workplace contributed to saving of costs associated with dental care. The workplace can be regarded as a key area for implementation of an oral health care system to make good use of limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 12 publications
2
30
0
8
Order By: Relevance
“…In a study of medical care costs in an occupational population, dental and medical healthcare costs for subjects with severe periodontitis were higher than those for subjects with no pathological pocketing 17) . It has been reported that oral health promotion programs in the workplace contribute to saving dental care costs 18) and are cost-beneficial for employers 19) . Therefore, heightening consciousness about oral health by oral health examination among the adult population may contribute to oral as well as systemic health and consequently may help to reduce dental and medical care costs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of medical care costs in an occupational population, dental and medical healthcare costs for subjects with severe periodontitis were higher than those for subjects with no pathological pocketing 17) . It has been reported that oral health promotion programs in the workplace contribute to saving dental care costs 18) and are cost-beneficial for employers 19) . Therefore, heightening consciousness about oral health by oral health examination among the adult population may contribute to oral as well as systemic health and consequently may help to reduce dental and medical care costs.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that participating in the program only once in 6 yr did not decrease dental expenses. This is because an employee's initial introduction to an oral health promotion program in the worksite leads to increased dental treatment and dental expense in the second year, as risk detection leads to an increase in the use of dental care services 16) . However, modified health behavior and increased awareness cannot be ensured through a single visit in 6 yr.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is important to show the benefits of oral health management programs to employers. There are many reports about the effects of activities promoting oral health [9][10][11][12][13][14] , but there are few reports concerning the effect of such activities on oral healthcare costs 15,16) . The purpose of this study is to examine whether oralhealth promotion programs provided as an occupational health service for employees are cost-beneficial for employers.…”
Section: Introductionmentioning
confidence: 99%
“…Em virtude disso, sabe-se que qualquer alteração nesse tripé irá causar desconforto e desequilíbrio para o indivíduo, prejudicando suas relações interpessoais, qualidade de vida e produção ocupacional 5 . Além disso, já está comprovado que a instituição de programas voltados para a promoção de saúde no local de trabalho é fundamental para o controle de diversas alterações da cavidade bucal, bem como na diminuição de idas do trabalhador aos serviços de saúde bucal 7 . Entre os limites desse estudo, deve-se salientar o uso de uma amostra de conveniência, o desenho de estudo de corte transversal e o seu caráter descritivo.…”
Section: Figura 1 -Composição Percentual Do Cpo-d Dos Trabalhadores Dounclassified
“…As doenças bucais comprometem a saúde geral do indivíduo, repercutindo de forma negativa na qualidade de vida e afetando a sua capacidade laborativa [3][4][5][6] . Por esses motivos é que vários estudos afirmam a necessidade de programas odontológicos nas empresas, diminuindo o afastamento desses trabalhadores do trabalho e melhorando o processo produtivo 7 . Assim como as doenças sistêmicas, as doenças bucais envolvem desde fatores ambientais, genéti-cos e imunológicos até fatores sociocomportamentais, a exemplo da vida social, hábitos de higiene oral e acesso à assistência odontológica.…”
Section: Introductionunclassified